DEVELOPMENT OF PHYSICS LEARNING TOOLS WITH GUIDED DISCOVERY MODELS ASSISTED BY INTERACTIVE SIMULATION - Patandean, Agustinus Jarak; Swandi, Ahmad; Rahmadhanningsih, Sri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to develop learning tools with Guided Discovery Model Assisted by Interactive Simulation (GDM-IS) on static fluid concepts. This research uses the 4D development method to produce learning tools but only carries out 3 stages, namely Define, Design and Development. At the development stage, validation is carried out on the GDM-IS learning tools that have been developed which include RPP, Student Worksheets (LKPD), Learning Media. Limited trial using a One Shoot Case Study research design. In this design, the learning instruments that have been developed are used in one class as a sample of 38 students. Data on science process skills was taken through observation by two observers. Based on the analysis of the validation results, the assessment of the RPP, LKPD and media is in a percentage above 80% which is in the valid (good) category.